TAKAYASUS’S ARTERITIS IN PREGNANCY – A RARE CASE REPORT - DR.SULOCHANA DASH; DR AKSHAYA KUMAR MAHAPATRO (International Journal of Pharma and Bio Sciences, 2014)
Takayasu’s areritis is a chronic inflammatory oblitarative arteritis of unknown aetiology. Anaesthesia in these patients is complicated by uncontrolled hypertension, hypoperfusion of organs and difficulty in BP monitoring due to stenosis and aneurismal dilatation of arteries. This case report is about successful management of a 27 yrs old primigragida with known case of Takayasu’s arteritis, Seizure disorder and Hypothyroidism at 38 wks of gestation on treatment who underwent an emergency caesarean section under spinal anaesthesia. The intraoperative and postoperative period was uneventful. Uniqueness of this case is maintenance of adequate mean arterial pressure in a hypothyroid patient with TA by adequate preloading and SAB with low dose local anaesthetic with a narcotic (fentanyl).